Synthesis and Characterization of Amorphous Silica Nanoparticles Production from Indonesia Coal Fly Ash - Yugo Chambioso; Ariadne Lakshmidevi Juwono; Amru Daulay (Journal of Chemical Natural Resources, 2025)
Coal fly ash an inexpensive waste material rich in silica, is reused as a renewable source and has attracted widespread attention. The sol-gel process was used to synthesize silica nanoparticles based on coal fly ash. Extraction of silica in the form of alkaline sodium silicate using alkali, followed by the formation of silica gel from the neutralization of alkaline sodium silicate with acid. The treated samples were calcined at 450 °C, 650 °C, and 850 °C. The chemical composition, morphology, phase, and silica functional groups of the as-synthesized silica nanoparticle powder were investigated using X-ray fluorescence (XRF), field emission scanning electron microscopy and Electron diffraction spectroscopy (FESEM-EDS), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). Infrared (IR) spectral analysis showed that silica had hydrogen-bonded silanol and siloxane groups. The silica nanoparticles' purity was found to be as high as 97% in their amorphous state, with XRD analysis indicating this due to the broad peak observed in the 20-23° two-theta region, characterised by a spherical shape and a tendency to aggregate into clusters.